Review of insider and insider threat detection in the organizations - Arshiya Subhani; Iftikhar Alam Khan; Anmol Zubair (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: The insider threat is a severe issue in cyber security. Protecting a company from the potentially disastrous actions of its own employees presents a formidable challenge, and identifying and eliminating the insider threat is a crucial part of that. This study aims to determine the types of insider threats that can exist within an organization and the best methods for countering them. Methodology: Insiders (representing types of insiders, motivation, insider access, methods used by insiders, insider profiling, and levels of insiders); Threat Detection Methods (describing methodology, techniques, datasets used to implement various insider threat detection techniques, and different analyzed user behavior); and Insider Threat Analysis (describing the various analyzed behavior of the user) are the three categories into which the research has been sorted. Findings: Since the global changes in the business environment, insider threats have become a problem for most companies. There has been an increase in the insider threat since 2019, and one primary reason is the widespread adoption of cloud computing and bring-your-own-device policies for remote work. Implications/Novel Contribution: Future studies are encouraged to improve threat detection methods, evaluate the efficacy of existing methods using a real-world dataset, and adopt a hybrid approach to developing effective models for detecting insider threats.